Including Persons with Disabilities in the Religious Community: Program Models Implemented by Two Churches - Collins, Belva C. (Journal of religion, disability & health, 2010)
Due to a mission to minister to the community, the religious community is one segment of society in which persons with disabilities may turn for support. Yet, many congregations create segregated programs for persons with disabilities, especially those with intellectual disabilities, instead of supporting them within inclusive activities. This article describes model efforts by two churches to change attitudes, raise sensitivity, and promote inclusive practices throughout their congregations. Suggestions are offered for others who wish to make similar changes in their own churches.